WARATIAN MEDIATION AS A FORM OF CONSOLIDATION OF MERCOSUR: THE SEARCH FOR AN EFFECTIVE SOCIAL INTEGRATION (Revista Direitos Humanos e Democracia, 2021)
The increasingly complex complexity of Latin American society makes us rethink the model of integration used by the European Union, since this has already proved to be inconsistent with the reality of the South American states. In the meantime, Luis Alberto Warat teaches that it is necessary that there be an emancipation of the Right, so that it recovers the sensibility that the rationalism has buried. The core of emancipation, therefore, would be alterity, and the possible path to emancipatory success would be mediation. Thus, it is hoped in this research to analyze how mediation, in Luis Alberto Warat, could function as a possible instrument for promoting social pacification, and also how it could solidify MERCOSUR, how proces of social integration. Therefore, we chose to carry out the present research from the perspective of a qualitative approach, through consultations in doctrine. It is also highlighted here, as one of the main theoretical contributions used, the studies of Luis Alberto Warat, especially in what concerns mediation.
Keywords: Harmonization; Culture of Peace; Mediation in Luis Alberto Warat; Mercosur; Conflict Transformation